Enhanced scanning electron microscopy images using muscovite mica, an example with Rhizaria. Issue 7 (3rd March 2022) - Llopis Monferrer, Natalia; Foulon, Valentin; Elies, Philippe
Abstract: Muscovite mica sheets were used as a support to capture scanning electron microscopy pictures of marine biological samples. The physical properties of the cleaved muscovite mica provide a clean background, which greatly reduces the postprocessing of images, thereby enhancing them and resulting in impressive images. We chose siliceous Rhizaria for this investigation due to their morphological diversity and elaborate skeletons. Research highlights: Muscovite mica sheet was used as a SEM support for biological sample Physical properties of muscovite mica sheet can provide native dark, gray, and white background of SEM images Muscovite mica sheet should be considered for image production in the context of art and science intersection Abstract : Schematic diagram showing the effect of tilt on the background colour of SEM images. When the sample is placed perpendicular to the electron beam (0° tilt), the mica sheet has a very clean and homogeneous dark black background. When the tilt angle is about 75°, the cleaved muscovite mica sheet produces a grey background. At a high angle of inclination near 90°, the very smooth mica is rendered white.